A destination choice model for very large gas carriers (VLGC) loading from the US Gulf. (1st May 2019) - Bai, Xiwen; Lam, Jasmine Siu Lee
Abstract: This study is one of the first to model energy shipping destination choice behaviors and identify their associations with various market factors from charterers' perspective. The paper uses very large gas carriers loading from the US Gulf as an illustration. Attributes include freight rate, propane price spread, bunker costs and number of ships in the destination areas. It also identifies the effects of the Panama Canal expansion on destination choices, by dividing sample data into two sub-periods: pre- and post-expansion. Furthermore, both aggregate and disaggregate analysis for different ports are provided. This work draws significant implications for energy transport planning. Understanding the charterer's choice of destinations is vital in determining traffic flow to a specific destination and in forecasting supply patterns. This model can be applied to other downstream commodity shipping segments with available arbitrage opportunities, less sticky trade flows and active traders. Highlights: Models energy shipping destination choice behaviors from charterers' perspective. Attributes include freight rate, propane price spread, bunker costs and the number of ships. Uses Automatic Identification System (AIS) data to analyze spatial patterns in seaborne energy transportation. Analyses effects of the Panama Canal expansion on destination choices. Segments with arbitrage, less sticky trade and active traders can use this model.